Provides for Inpatients' Self-Care Needs - Kamesyworo; Zikiriyani, Imas (International Journal Scientific and Professional, 2023)
Self-care deficit is a person's inability to fulfill basic self-care needs independently. The aim of the research is to obtain an overview of the implementation of nursing needs to fulfill self-care needs in patients with self-care deficit. Descriptive research, with an implementation method using nursing care, with a process of assessment, interviews and direct observation carried out from 12 to 18 April 2021. The case study subjects were two schizophrenic patients with self-care deficit problems in the Stork Room at Ernaldi Hospital Bahar, South Sumatra Province. The results of this study indicate that fulfilling self-care needs is very effective in overcoming the problem of self-care deficit.